Analysis of Ultrasonographic Characteristics of Early Hepatic Alveolar Echinococcosis - Wang, Yong-Xing; Liu, Wei; Sun, Zhan-Yong; Wu, Lan; Xie, Xian-Kun; Liu, Bo (Frontiers in Surgery, 2022)
Objective: This study aims to investigate the ultrasonographic characteristics of early hepatic alveolar echinococcosis (HAE) and improve the qualitative diagnostic ability of sonographers. Methods: The data of 80 positive cases of HAE screened and diagnosed by ultrasonography and serum immunology (33 males and 44 females with a mean age of 44.12 ± 14.31 y) were used in the study. The imaging characteristics of the lesions (i.e., intrahepatic distribution, shape, size, echo, blood flow, and growth characteristics) were analyzed retrospectively, and the ultrasonographic characteristics of early lesions were discussed in combination with their basic pathological changes. Results: Patients with lesions of the proliferative infiltration type accounted for 57.5% (46/80), the fibrous calcification type accounted for 26.25% (21/80), the necrotic liquefaction type accounted for 6.25% (5/80), and the mixed type accounted for 10% (8/80). Patients with lesions involving the right lobe and the left lobe accounted for 76.25% (61/80) and 11.25% (9/80), respectively, and with lesions involving both the left and right lobes accounted for 12.5% (10/80). There were statistically significant differences in diameter between all types of lesions (n = 88; F = 5.926 and P = 0.004). Focal hyperechoic and diffuse heterogenous nodular changes were the main manifestations of early proliferative infiltration lesions. Conclusion: Ultrasonography is extremely valuable in the diagnosis of early HAE. Capillary hemangioma-like changes and hailstorm sign are the main characteristics of early lesions of HAE, and calcification is a common concomitant sign.